2010
DOI: 10.1074/jbc.m110.102947
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Dendritic Cell Development by Bacterial Fermentation Products Butyrate and Propionate through a Transporter (Slc5a8)-dependent Inhibition of Histone Deacetylases

Abstract: Mammalian colon harbors trillions of bacteria, yet there is no undue inflammatory response by the host against these bacteria under normal conditions. The bacterial fermentation products acetate, propionate, and butyrate are believed, at least in part, to be responsible for these immunosuppressive effects. Dendritic cells play an essential role in presentation of antigens to T lymphocytes and initiation of adaptive immune responses. Here we report that butyrate and propionate block the generation of dendritic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
165
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(181 citation statements)
references
References 50 publications
2
165
0
2
Order By: Relevance
“…Other studies have also demonstrated a reduction in DC development and activation. [32][33][34] Furthermore, we observed that SCFA-treated APC induced less proliferation of CD4 + and CD8 + T lymphocytes, demonstrating that the modulation of DC treated with SCFAs was functional. DC links innate immunity Figure 7.…”
Section: Discussionmentioning
confidence: 68%
“…Other studies have also demonstrated a reduction in DC development and activation. [32][33][34] Furthermore, we observed that SCFA-treated APC induced less proliferation of CD4 + and CD8 + T lymphocytes, demonstrating that the modulation of DC treated with SCFAs was functional. DC links innate immunity Figure 7.…”
Section: Discussionmentioning
confidence: 68%
“…A balanced combination of diet containing epigenetic nutaceuticals and food based probiotics not only can save from various gut pathogenesis rather it can act as prophylactic. The role of epigenetic nutraceuticals in the alterations of epigenetic composition of human genome leaves a great future for the researchers in the field [116][117][118][119][120][121][122]. Further understanding of molecular cross talk of epigenetic nutraceuticals with the microbiome epigenome and cellular millue of gut can lead to the development of disease specific formulations of natural mrdicine.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…However, butyrate does not affect the process of histone acetylation itself; therefore, the increase in half-life is due to inhibition of HDACs (11). HDAC inhibition is believed to be mediated directly by SCFAs, independent of GPCRs, based on the requirement for SLC5A8 for SCFA entry into colonocytes and subsequent HDAC inhibition (68); however, there is also evidence from another group that Gpr41 may help mediate SCFA effects on HDAC (86). 3-Hydroxy butyrate (␤-hydroxybutyrate), a structurally similar ketone intermediate endogenously produced during starvation and diabetes, inhibits class I HDAC in HEK293T cells (65).…”
Section: Modulation Of Histone Acetylation By Scfasmentioning
confidence: 99%